2016
DOI: 10.18311/mvpjms/2016/v3/i1/739
|View full text |Cite
|
Sign up to set email alerts
|

Study of Correlation of Cord Blood Bilirubin with Neonatal Hyperbilirubinemia

Abstract: Introduction: Neonatal Hyperbilirubinemia (NH) is a universal problem affecting nearly 60% of term and 80% of preterm neonates during first week of life. Early discharge of healthy term newborns is a common practice because of medical, social and economic constraints. Insignificant number (6.5%) of babies, NH is a cause for readmission. The present study was conducted to correlate the Cord Blood Bilirubin (CBB) level with subsequent NH. Methods: Study was performed at the Department of Pediatrics in a Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 17 publications
0
14
2
1
Order By: Relevance
“…Severe hyperbilirubinemia can occur without apparent reason in healthy infants, and some may develop kernicterus. 1 The prevention of poor outcomes necessitates early detection of neonates who are at risk of developing significant hyperbilirubinemia.…”
Section: Introductionmentioning
confidence: 99%
“…Severe hyperbilirubinemia can occur without apparent reason in healthy infants, and some may develop kernicterus. 1 The prevention of poor outcomes necessitates early detection of neonates who are at risk of developing significant hyperbilirubinemia.…”
Section: Introductionmentioning
confidence: 99%
“…10 In another Indian study by Ahire N et al reported sensitivity of 100%, specificity of 98.17% and positive predictive value of 66.67%, negative predictive value of 100% using cord bilirubin cut-off ≥3 mg/dL. 11 Thus, it can be seen that different authors have used different cut-off value for predicting significant jaundice. Bilirubin estimation varies from laboratory to laboratory, depends on methods used, technical error, ethnic makeup of people, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff value for prediction of hyperbilirubinemia is different in different studies. Prospective study conducted by Ahire reported that neonates with cord blood bilirubin ≥ 3mg/dl should be monitored more frequently [10]. The cut-off point for cord blood bilirubin in full-term neonates was given as 2.15 mg/dl in another prospective clinical study [8].…”
Section: Discussionmentioning
confidence: 99%